2016
DOI: 10.4236/cweee.2016.54010
|View full text |Cite
|
Sign up to set email alerts
|

Water Resource Pricing Study Based on Water Quality Fuzzy Evaluation: A Case Study of Hefei City

Abstract: Price plays an important role in water resources management. The price of water resources can also be considered as a "water resource tax" which reflects the value and opportunity cost of water, and people will pay for the right to use water. Currently, the water resource fees' effect of regulating resource differential revenues is not manifest and it's not enough to reflect the principle of paid use of resources as well as regulating resources differential revenues. Due to the ambiguity and complexity of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Zero-order reactions may be expressed as Required hydraulic detention time for various orders of reaction also depicted in Figure 5, which is very useful for water treatment reactor. There are several further computational hydraulics applications that address water quality concerns [9].…”
Section: Hydraulics Used In Water Supply and Treatmentmentioning
confidence: 99%
“…Zero-order reactions may be expressed as Required hydraulic detention time for various orders of reaction also depicted in Figure 5, which is very useful for water treatment reactor. There are several further computational hydraulics applications that address water quality concerns [9].…”
Section: Hydraulics Used In Water Supply and Treatmentmentioning
confidence: 99%
“…The authors found that the economic impacts of improvement and stabilization of water quality in the lake are substantial, and that the additional property tax benefits generated by water quality improvements would be sufficient to cover the costs of creating the improvement. Duan and Liu (2016) used methods relating to fuzzy mathematics for modeling and to study processing water resource pricing in the City of Hefei, China. The evaluation had a comprehensive consideration of five factors including water quality, water resources per capita, household consumption level, per capita gross national product (GNP), and population or population density to evaluate the water resource price.…”
Section: Water Supply Policiesmentioning
confidence: 99%